2012
DOI: 10.1111/j.1742-7843.2011.00852.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Vitamin C Deficiency does not Accelerate Oxidative Stress in Ageing Brains of Guinea Pigs

Abstract: Increased oxidative stress in the brain has consistently been implied in ageing and in several degenerative brain disorders. Acting as a pivotal antioxidant in the brain, vitamin C is preferentially retained during deficiency and may play an essential role in neuroprotection during ageing. Thus, a lack of vitamin C could be associated with an increase in redox imbalance in the ageing brain. The present study compared oxidative stress of ageing to that of a long-term non-scorbutic vitamin C deficiency in guinea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 44 publications
5
22
0
Order By: Relevance
“…A study with Svct2 +/− mice compared to wild type demonstrated that VitC levels in brain cortex were genotype dependent with higher VitC content in mice homozygous for Svct2 (+/+) compared to heterozygous counterparts [18], supporting the SVCT2 as the predominant active transporter to the brain. This is in agreement with findings of undetectable mRNA levels of SVCT1 (which is present in other organs, e.g., the liver) in guinea pig brain homogenate [19] Within the brain differential VitC retention in specific brain regions has been reported [20]. Dietary intervention studies have shown increases in Svct2 mRNA expression in the liver, both in vitro and in vivo , but not in the brain following VitC deficiency in mice unable to synthesize VitC ( Gulo −/− ) [21,22].…”
Section: Introductionsupporting
confidence: 92%
“…A study with Svct2 +/− mice compared to wild type demonstrated that VitC levels in brain cortex were genotype dependent with higher VitC content in mice homozygous for Svct2 (+/+) compared to heterozygous counterparts [18], supporting the SVCT2 as the predominant active transporter to the brain. This is in agreement with findings of undetectable mRNA levels of SVCT1 (which is present in other organs, e.g., the liver) in guinea pig brain homogenate [19] Within the brain differential VitC retention in specific brain regions has been reported [20]. Dietary intervention studies have shown increases in Svct2 mRNA expression in the liver, both in vitro and in vivo , but not in the brain following VitC deficiency in mice unable to synthesize VitC ( Gulo −/− ) [21,22].…”
Section: Introductionsupporting
confidence: 92%
“…That outcome is consistent with our results in the mouse liver. Moreover, since Tveden-Nyborg et al reported that a chronic AA deficiency did not change lipid oxidation levels in livers from guinea pigs (41), an AA deficiency may specifically affect the oxidation of proteins but not lipids in the liver. Tanaka et al described the interactions between AA and vitamin E after using ODS rats fed an AA-free and vitamin E-free diet (42).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, as both rat and mouse models are capable of synthesizing VitC, results should be interpreted with caution as the findings may not translate well to humans. In aging guinea pigs subjected to long term, non-scorbutic VitC deficiency (100 mg VitC/kg feed), no significant effects of age on biochemical markers in the brain were detected compared to controls (323 mg VitC/kg feed), and it was concluded that the age-related change in VitC status observed in several species is more likely related to maturation rather than aging per se [115,116]. …”
Section: Vitamin C Deficiency and Cognitive Dysfunctionmentioning
confidence: 99%